Kajian Pemeliharaan Bangunan Gedung Bandara Pattimura Kota Ambon - Samsul Bahri Keledar; Fauzan A. Sangadji; Imran Oppier (Publikasi Indonesia, 2021)
All buildings built by humans can of course be damaged where the damage that occurs to buildings is caused by a decrease in quality and increasing age of a building, but the quality and age of buildings can be improved and maintained by carrying out periodic repairs and maintenance. This study aims to identify the percentage of suitability for the implementation of maintenance and maintenance activities for the Ambon Pattimura Airport building based on maintenance guidelines and applicable regulations. The analytical method used in this study is a quantitative descriptive analysis method. The analytical tool used was factor analysis using the IBM SPSS version 21 tool. Based on the results of the study it can be concluded that the percentage of maintenance for the Pattimura International Airport building, Ambon City, has 2 instruments from the architectural component, namely x1.1 maintenance of egress facilities by 85.83% and x1.3 maintenance of ceramic/mosaic walls (bathroom walls, toilets, etc.) of 85%.